2016
DOI: 10.1007/s11914-016-0308-1
|View full text |Cite
|
Sign up to set email alerts
|

The Skeletal Effects of Inhaled Glucocorticoids

Abstract: The skeletal effects of inhaled glucocorticoids are poorly understood. Children with asthma treated with inhaled glucocorticoids have lower growth velocity, bone density, and adult height. Studies of adults with asthma have reported variable effects on BMD, although prospective studies have demonstrated bone loss after initiation of inhaled glucocorticoids in premenopausal women. There is a dose response relationship between inhaled glucocorticoids and fracture risk in asthmatics; the risk of vertebral and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 73 publications
0
21
1
2
Order By: Relevance
“…Long-term use of OCS may also induce other adverse effects; for example, it was reported that morbidity rates for patients with severe asthma comorbid with other diseases, such as type-2 diabetes, dyspeptic disorder, and cataract, prescribed with higher OCS dose were significantly higher than those with mild/moderate asthma. Glucocorticoid highly decreases bone formation by inhibiting cell differentiation, and increasing apoptosis might be the mechanism causing such an effect [ 67 ]. Consistent to previous investigations, our study showed that the cumulative doses of OCS and ICS were significantly higher for patients with fracture than those without fracture, indicating the dose-response effects (Tables 5 and 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term use of OCS may also induce other adverse effects; for example, it was reported that morbidity rates for patients with severe asthma comorbid with other diseases, such as type-2 diabetes, dyspeptic disorder, and cataract, prescribed with higher OCS dose were significantly higher than those with mild/moderate asthma. Glucocorticoid highly decreases bone formation by inhibiting cell differentiation, and increasing apoptosis might be the mechanism causing such an effect [ 67 ]. Consistent to previous investigations, our study showed that the cumulative doses of OCS and ICS were significantly higher for patients with fracture than those without fracture, indicating the dose-response effects (Tables 5 and 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was noted that the prevalence of asthma in patients with fracture was significantly lower than those without fracture, while COPD was more prevalent in patients with fracture than those without fracture. With regard to bronchiectasis, although it was more prevalent in patients with fracture, but not reaching significance, the inconsistency might be caused by a difficulty in differentiating skeletal effects of corticosteroid medications and COPD itself [ 67 ] and symptoms of COPD overlapped with asthma [ 77 , 78 ] or bronchiectasis [ 79 , 80 ] for some patients. The mortality rate of bronchiectasis was reported to be as high as 20.4% and increased to 55% if comorbid with COPD [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…None of these subjects, however, were treated with high dosages or with oral glucocorticoids. Because the impact of inhaled glucocorticoids was regarded to be minimal, we did not exclude them from the study. Furthermore, the selection of the mutation‐negative individuals for the control group was based solely on family relations, in order to have groups with similar overall genetic backgrounds, while disregarding age, gender, or menopausal status as inclusion or exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis has been linked with asthma as well, mainly due to chronic corticosteroid therapy ( 55 57 ); yet musculoskeletal complications of inhaled corticosteroids are highly debatable ( 55 , 58 ). Lower bone mineral density in adult asthmatic patients using inhaled glucocorticoids compared to untreated controls has been described ( 57 , 59 , 60 ), even though this finding was not uniform ( 61 , 62 ).…”
Section: Metabolic Disorders and Asthmamentioning
confidence: 99%
“…Lower bone mineral density in adult asthmatic patients using inhaled glucocorticoids compared to untreated controls has been described ( 57 , 59 , 60 ), even though this finding was not uniform ( 61 , 62 ). A dose response relationship between use of oral glucocorticoids with risk of fracture in patients and asthma has been extensively validated ( 55 , 63 ).…”
Section: Metabolic Disorders and Asthmamentioning
confidence: 99%